(untitled) (Archaeologia Adriatica, 2020)
The paper offers a discussion on symbolical, solar structure of compositions on ceramic vessels from Sala Consilina (Campania) and from grave III from S. Maria d’ Anglone (Basilicata). They were both made in the Middle Geometric expression (Geometrico Medio, a tenda: last decades of the 9th cent. BC and the first half of the 8th cent. BC) in the complex of matt-painted pottery with geometrical motifs from southern Italy. The compositions were named solar landscapes because in the language of "abstract narration" in a meaningful compositional game (story) of symbolical horizontals and verticals accompanied by typical solar symbols, they depict crucial movements of the Sun: rise on the horizon, its worship and impact on lower spheres: earthly, chthonic (?). Thereby the main motif – concave a tenda ("tent-shaped") triangle symbolizes rising of mighty Sun energy on the horizon from celestial waters. This is a semantical origin of the entire a tenda expression with its many variants. Despite regional particularities of autochtonous painting on pottery of southern Italy, where the symbolical and the decorative have alternated for years, we can conclude that artistic concept of solar landscape, with a tenda triangle or without it, was its important iconographic, stylistic and semantical component that was born from religion.